Measurement of γ+b+X and γ+c+X production cross sections in pp̄ collisions at s=1.96TeV - Abazov, V. M. (2009)
First measurements of the differential cross sections d3σ/ (dpTγdyγdyjet) for the inclusive production of a photon in association with a heavy quark (b, c) jet are presented, covering photon transverse momenta 30<pTγ<150GeV, photon rapidities |yγ|<1.0, jet rapidities |yjet|<0.8, and jet transverse momenta pTjet>15GeV. The results are based on an integrated luminosity of 1fb-1 in pp̄ collisions at s=1.96TeV recorded with the D0 detector at the Fermilab Tevatron Collider. The results are compared with next-to-leading order perturbative QCD predictions. © 2009 The American Physical Society.